MRI assessment of the postprandial gastrointestinal motility and peptide response in healthy humans. Issue 1 (31st August 2017) - Khalaf, A.; Hoad, C. L.; Menys, A.; Nowak, A.; Taylor, S. A.; Paparo, S.; Lingaya, M.; Falcone, Y.; Singh, G.; Spiller, R. C.; Gowland, P. A.; Marciani, L.; et al.
Abstract: Background: Feeding triggers inter‐related gastrointestinal (GI) motor, peptide and appetite responses. These are rarely studied together due to methodological limitations. Recent MRI advances allow pan‐intestinal, non‐invasive assessment of motility in the undisturbed gut. This study aimed to develop a methodology to assess pan‐intestinal motility and transit in a single session using MRI and compare imaging findings to GI peptide responses to a test meal and symptoms in a healthy volunteer cohort. Methods: Fifteen healthy volunteers (29.3±2.7 years and BMI 20.1±1.2 kg m −2 ) underwent baseline and postprandial MRI scans, symptom questionnaires, and blood sampling (for subsequent GI peptide analysis, Glucagon‐like peptide‐1 [GLP‐1], Polypeptide YY [PYY], Cholecystokinin [CCK]) at intervals for 270 minutes following a 400 g soup meal (204 kcal, Heinz, UK). Gastric volume, gall bladder volume, small bowel water content, small bowel motility, and whole gut transit were measured from the MRI scans. Key Results: (mean±SEM) Small bowel motility index increased from fasting 39±3 arbitrary units (a.u.) to a maximum of 87±7 a.u. immediately after feeding. PYY increased from fasting 98±10 pg mL −1 to 149±14 pg mL −1 at 30 minutes and GLP‐1 from fasting 15±3 μg mL −1 to 22±4 μg mL −1 . CCK increased from fasting 0.40±0.06 pmol mL −1 to 0.94±0.1 pmol mL −1 . Gastric volumes declined with a T1/2 of 46±5 minute and the gallbladder contracted from a fasting volume of 19±2 mL −1 to 12±2 mL −1 . Small bowel water content increased from 39±2 mL −1 to 51±2 mL −1 postprandial. Fullness VAS score increased from 9±5 mm to 41±6 mm at 30 minutes postprandial. Conclusions and Inferences: The test meal challenge was effective in inducing a change in MRI motility end‐points which will improve understanding of the pathophysiological postprandial GI response. Abstract : Motility assessment. Reference image (A) and a motility map (B) for a healthy volunteer. ROIs were placed on the reference image to include small bowel loops only.